Pengaruh Lokasi, Harga, Promosi, dan Kualitas Produk terhadap Loyalitas Konsumen dengan Kepuasan sebagai Variabel Intervening: Studi Kasus UD Club Parfum Lubuk Pakam - Aisyah, Siti; Marliyah, Marliyah; Tanjung, Selvira Wardani (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to examine how location, price, promotion and product quality influence customer loyalty, with satisfaction as an intervening variable (case study at UD Club Parfum Lubuk Pakam). Quantitative methods with an associative approach were used in this research. Data was collected through questionnaires, observation and documentation, with 361 respondents participating. Data analysis was carried out using the Structural Equation Modeling-Partial Least Square (SEM-PLS) technique, with hypothesis analysis using the t test, coefficient of determination (R2), and the Intervening test presented via the SmartPLS 3.0 application. The research results show that location, price and promotion have a positive and significant influence on customer satisfaction. Meanwhile, product quality has a negative and significant influence on satisfaction. In terms of customer loyalty, price has a significant negative influence, while promotion has a positive and significant influence. Location and product quality do not have a significant influence on customer loyalty. Customer loyalty is positively influenced by the level of satisfaction. In conclusion, location, price and promotion have a positive and significant impact on customer loyalty through satisfaction, while product quality has a negative and significant impact on customer loyalty through satisfaction.